Pelaksanaan Pembelajaran Pendidikan Agama Islam pada Anak Berkebutuhan Khusus di SMP Negeri 6 Pekanbaru - Miftahul Husni; Gusma Afriani (Lembaga Anotero Scientific Pekanbaru, 2021)
It was quantitative descriptive research. This research aimed at knowing how the implementation process of Islamic Education learning on children with special needs at State Junior High School 6 Pekanbaru was. The subject of this research was an Islamic Education subject teacher, and the object was the implementation of Islamic Education learning on children with special needs at State Junior High School 6 Pekanbaru. An Islamic Education subject teacher was the population of this research. Because the number of the population was small, Total sampling technique was used in this research, all population members were selected as the samples. Questionnaire, interview, and documentation were the techniques of collecting the data. The research findings showed that the implementation of Islamic Education learning on children with special needs at State Junior High School 6 Pekanbaru same as the implementation of learning at the reguler class generaly. The teacher did a planing by using the same lesson plan, but different in indicators between student reguler class and slow learner. The teacher using demontration method, question and answer, and giving the task, teacher using whiteboard, LCD, laptop media and and simple media tool. Teacher using a media appropriate to the learning material. Video media was the pavorite media by reguler and slow learner student. In the implemention of learning, slow learner did not accompanied by a special companion teacher because in this school did not had a special companion teacher.